The Effect of Intellectual Capital and Corporate Social Responsibility on Firm Value: Managerial Ownership as Moderating Variable - Eka Widiati; Saminem (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2022)
Company value plays a critical role in the company's performance because an increase in company value indicates an increase in company performance. The purpose of this research is to determine the impact of intellectual capital and corporate social responsibility on firm value, with managerial ownership serving as a moderating variable. In this study, firm value was calculated using the Tobin's Q method and secondary data obtained from the IDX website. The research sample included 30 LQ45 companies listed on the Indonesia Stock Exchange from 2016 to 2020, chosen using a purposive sampling method. Multiple linear regression and moderated regression analysis were used to analyze the data, which was processed using SPSS 26 software. According to the findings of this study, intellectual capital has an impact on firm value. Meanwhile, corporate social responsibility has no effect on the company's value. Furthermore, the findings of this study show that managerial ownership can moderate the relationship between intellectual capital and firm value but cannot moderate the relationship between corporate social responsibility and company value. Based on the findings of this study, company executives should be able to maximize the value of VAIC in order to create the greatest value space between the three components of intellectual capital, namely human capital, structural capital, and capital employed. Keywords: Firm Value, Intellectual Capital, Corporate Social Responsibility, Managerial Ownership